Prepared to Ensure Quality Education for All? A Comparative Study of Pre-Service Teachers’ Self-Efficacy for Inclusion in Spain and the United States - Cristina Miralles-Cardona; María-Cristina Cardona-Moltó; Renáta Tichá; Brian H. Abery (Education Sciences, 2025)
The 2030 Agenda for Sustainable Development calls for quality, inclusive education for all through Sustainable Development Goal 4 (SDG 4). Given the central role of teachers in achieving this goal, this study examined (1) whether pre-service elementary teachers develop self-efficacy for inclusive teaching by graduation and (2) whether self-efficacy varies according to the type of teacher education program (general vs. dual) and the opportunities provided to learn inclusive teaching strategies. Using a non-experimental, cross-sectional comparative design, we surveyed 330 pre-service elementary teachers in the United States and Spain, enrolled in two distinct teacher education pathways. Participants completed the Teacher Self-Efficacy for Inclusive Practice (TEIP) and Opportunity to Learn to Teach Inclusively (OLTI) scales. Results revealed moderate levels of self-efficacy for inclusive teaching overall. Spanish participants in general teacher education programs reported significantly lower self-efficacy than U.S. participants in dual certification programs. Regardless of program type, those with greater opportunities to learn inclusive teaching strategies reported significantly higher self-efficacy. Notably, opportunity to learn was found to moderate the relationship between program type and self-efficacy. These findings highlight the critical role of practice-based opportunities in developing teachers’ confidence in inclusive education. Embedding such opportunities in teacher preparation is essential for advancing sustainable, inclusive education systems worldwide.